Exenatide Improves Bone Quality in a Murine Model of Genetically Inherited Type 2 Diabetes Mellitus - Pereira, Marie; Gohin, Stephanie; Roux, Jean-Paul; Fisher, Amy; Cleasby, Mark E.; Mabilleau, Guillaume; Chenu, Chantal (Frontiers in Endocrinology, 2017)
Type 2 diabetes mellitus (T2DM) is associated with skeletal complications, including an increased risk of fractures. Reduced blood supply and bone strength may contribute to this skeletal fragility. We hypothesised that long-term administration of Exenatide, a glucagon-like peptide-1 receptor agonist, would improve bone architecture and strength of T2DM mice by increasing blood flow to bone, thereby stimulating bone formation. In this study, we used a model of obesity and severe T2DM, the leptin receptor-deficient db/db mouse to assess alterations in bone quality and hindlimb blood flow and to examine the beneficial effects of 4 weeks administration of Exenatide. As expected, diabetic mice showed marked alterations in bone structure, remodelling and strength, and basal vascular tone compared to lean mice. Exenatide treatment improved trabecular bone mass and architecture by increasing bone formation rate, but only in diabetic mice. Although there was no effect on hindlimb perfusion at the end of this treatment, Exenatide administration acutely increased tibial blood flow. While Exenatide treatment did not restore the impaired bone strength, intrinsic properties of the matrix, such as collagen maturity, were improved. The effects of Exenatide on in vitro bone formation were further investigated in primary osteoblasts cultured under high glucose conditions, showing that Exenatide reversed the impairment in bone formation induced by glucose. In conclusion, Exenatide improves trabecular bone mass by increasing bone formation and could protect against the development of skeletal complications associated with T2DM.